PENGARUH MODAL KERJA DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Budi Setyawan (Politeknik Ubaya, 2021)
Abstract This study was conducted to determine the influence of working capital and profitability on firm value, either partially or simultaneously on the issuers of the Textile and Garment Sector at the Indonesia Stock Exchange. The data collection method used was documents studies, using secondary data in the form of financial reports from the Indonesia Stock Exchange. The data obtained were then processed by multiple regression method with SPSS software version 23.00. The results showed that working capital partially had no significant effect on firm value. Profitability partially has a significant effect on firm value. Simultaneously working capital and profitability have a significant effect on firm value. Keywords: Working Capital, Profitability, Firm Value